Contested Justice The Politics and Practice of International Criminal Court Interventions - De Vos, Christian; Kendall, Sara; Stahn, Carsten (Social Sciences, 2015)
This pioneering edited collection from scholars and practitioners who specialise in the work of the International Criminal Court brings together diverse approaches from law, anthropology, sociology and international relations to assess the social and political effects of this form of post-conflict justice. This title is also available as Open Access.